Odpowiedzi

Najlepsza Odpowiedź!
2010-01-28T15:56:03+01:00
(x-3)² - 9 +(y-1)² -1 + 2 = 0
(x - 3)² + (y - 1)² = 8
x + 3y + 2 = 0
x = -3y - 2
x- 3 = -3y - 2 -3 = -3y - 5
(-3y -5)² +(y-1)² = 8
9x² + 30 x +25 + y² -2y + 1 = 8
10 y² +28 y + 18 = 0
5 y² + 14 y + 9 = 0
Δ = 14² - 4*5*9 = 196 - 180 = 16
√Δ = √16 = 4
y1 = [-14 -4]/10 = -18/10 = -1,8
y2 = [-14 +4]/10 = -10/10 = -1
x1 = -3*(-1,8) -2 = 5,4 - 2 = 3,4
x2 = -3*(-1) - 2 = 3 - 2 = 1
A = (1; -1) , B = (3,4 ; -1,8)
wektor AB = [3,4 -1; -1,8 +1] = [2,4 ; 0,8]
I AB I² =(2,4)² + 0,8² = 5,76 + 0,64 = 6,4
I AB I = √(6,4) = 8/√10 = [8*√10]/10 = 0.8*√10.
Odp. Długość cięciwy AB jest równa 0,8 √10.
1 1 1